Heterotelechelic homopolymers mimicking high χ – ultralow N block copolymers with sub-2 nm domain size. Issue 14 (21st March 2022) - Hancox, E.; Derry, M. J.; Greenall, M. J.; Huband, S.; Al-Shok, L.; Town, J. S.; Topham, P. D.; Haddleton, D. M.
Abstract : Three fluorinated, hydrophobic initiators have been used for the synthesis of low molecular mass fluoro-poly(acrylic acid) heterotelechelic homopolymers to mimic high chi ( χ )–low N diblock copolymers with ultrafine domains of sub-2 nm length scale. Abstract : Three fluorinated, hydrophobic initiators have been utilised for the synthesis of low molecular mass fluoro-poly(acrylic acid) heterotelechelic homopolymers to mimic high chi ( χ )–low N diblock copolymers with ultrafine domains of sub-2 nm length scale. Polymers were obtained by a simple photoinduced copper(ii )-mediated reversible-deactivation radical polymerisation (Cu-RDRP) affording low molecular mass (<3 kDa) and low dispersity ( Đ = 1.04–1.21) homopolymers. Heating/cooling ramps were performed on bulk samples ( ca. 250 μm thick) to obtain thermodynamically stable nanomorpologies of lamellar (LAM) or hexagonally packed cylinders (HEX), as deduced by small-angle X-ray scattering (SAXS). Construction of the experimental phase diagram alongside a detailed theoretical model demonstrated typical rod–coil block copolymer phase behaviour for these fluoro-poly(acrylic acid) homopolymers, where the fluorinated initiator-derived segment acts as a rod and the poly(acrylic acid) as a coil. This work reveals that these telechelic homopolymers mimic high χ -ultralow N diblock copolymers and enables reproducible targeting of nanomorphologies with incredibly small, tunable domain size.